2021
DOI: 10.1111/camh.12474
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of a new behavioural activation programme for young people with depressed mood

Abstract: Background: Behavioural activation (BA) is effective in adults with depression but the evidence for young people (YP) is less clear. We therefore developed and tested a new coproduced BA programme. Method: In phase one (2014 to 2015 inclusive), we codeveloped with young people attending specialist child and adolescent mental health service (CAMHS) an 8-session BA workbook. In Phase two (2019 to 2020 inclusive), we ran an uncontrolled feasibility study in two specialist CAMHS, with BA being offered to YP by les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Full details of patients included are published in the outcome paper. 20 In brief, 33 young people aged 12–17 years were involved; 11 were male (33%) and 22 were female (67%); and patients were of mixed (White and Asian) ( n = 2), Asian ( n = 2), Black (African) ( n = 1) or White British ( n = 28) ethnicity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Full details of patients included are published in the outcome paper. 20 In brief, 33 young people aged 12–17 years were involved; 11 were male (33%) and 22 were female (67%); and patients were of mixed (White and Asian) ( n = 2), Asian ( n = 2), Black (African) ( n = 1) or White British ( n = 28) ethnicity.…”
Section: Resultsmentioning
confidence: 99%
“…It was part of a wider feasibility study. 20 This study adds to the limited research that has used the TDF to investigate barriers and facilitators to implementing psychological therapies, 9 , 43 and, to our knowledge, is the first study to specifically investigate the implementation of a behavioural activation intervention. A strength of this study is that it demonstrated how the novel TTT can be used to systematically identify and link TDF domains to evidence-based BCTs, which can be used to overcome barriers and support facilitators of implementing a new intervention into clinical practice.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Only one study has interviewed parents/carers of young people with depression undertaking BA (Dubicka et al, 2022) and very few studies sought feedback from young people who have experienced support and therapist preconceptions against manualised therapy or BA. Conclusions: Manualised BA for young people requires flexibility and adjustment to meet individual and family needs.…”
Section: Introductionmentioning
confidence: 99%